Interprofessional Collaboration Between a Clinical Pharmacist and Specialty Physicians to Treat Hepatitis C in an Interdisciplinary Medical Practice Setting. (December 2022) - Fix, Jennifer T.; Hauf, Steven; Herrera, Michael; Martin, Randy; Sweeden, Mason; Meyer, Karl
Objective: Describes the activities of a clinical pharmacist in a gastroenterology (GI) clinic providing services to hepatitis C virus (HCV) patients, with a focus on practice management activities and tools.Practice Description: Located inside a GI specialty clinic in Fort Worth, Texas, the pharmacist provides comprehensive medication management under a collaborative practice agreement (CPA). Once referred by the GI physician, the pharmacist has face-to-face patient visits, develops the care plan, orders medications, and follows patients through sustained virologic response and the development of a hepatocellular carcinoma surveillance plan.Practice Innovation: The role of pharmacists in the management of HCV is important to understand. This article details a pharmacist-led clinic in an open GI medical practice.Evaluation: A retrospective chart review study was conducted to assess outcomes related to the integration of the clinical pharmacist.Methods: Completed by the study team, this study included manual chart reviews of patients with the ambulatory care pharmacist-driven HCV practice to pull data and information that were then tabulated using Qualtrics.Results: A total of 95 charts were surveyed, 78 records were created, and 49 patients were started on direct-acting antiviral (DAA) treatment by the pharmacist. Patients required multiple pharmacist communication actions. The minimum duration of the pharmacist service was 6 months and could extend more than 9 months depending on the time it took to get the patient started on medication. Pharmacist integration into the practice resulted in improved intake for the GI clinic, improved interprofessional interaction, and increased utilization of newer treatment modalities for HCV which feature cure rates up to 99% with limited side effects.Conclusion: Clinical pharmacists are well positioned to help navigate patients through the complexities of the medication use system, medication access, drug interactions and adverse effects, promote medication adherence, and allow patients to start and complete therapy.